2016
DOI: 10.4103/0019-5413.185604
|View full text |Cite
|
Sign up to set email alerts
|

Limb lengthening in achondroplasia

Abstract: Background:Stature lengthening in skeletal dysplasia is a contentious issue. Specific guidelines regarding the age and sequence of surgery, methods and extent of lengthening at each stage are not uniform around the world. Despite the need for multiple surgeries, with their attendant complications, parents demanding stature lengthening are not rare, due to the social bias and psychological effects experienced by these patients. This study describes the outcome and complications of extensive stature lengthening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
18
1
3
Order By: Relevance
“…In addition, abnormal chondrocyte hypertrophy and transition to bone is associated with fibrocartilage and fibrous tissue accumulation that also interferes with bone bridging, revealing a central role of FGFR3 signaling in controlling the balance between ossification and fibrosis. These findings have major impacts on the management of patients affected with achondroplasia that may require surgery for limb lengthening as managing the level of stabilization and endochondral ossification may be crucial to allow successful healing ( Chilbule et al., 2016 ; Kitoh et al., 2014 ). Beyond this specific clinical setting, the results bring fundamental insights on the mechanisms of bone repair defects in pseudarthrosis and the role of PCs and FGFR3 in the essential step of cartilage-to-bone transformation during bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abnormal chondrocyte hypertrophy and transition to bone is associated with fibrocartilage and fibrous tissue accumulation that also interferes with bone bridging, revealing a central role of FGFR3 signaling in controlling the balance between ossification and fibrosis. These findings have major impacts on the management of patients affected with achondroplasia that may require surgery for limb lengthening as managing the level of stabilization and endochondral ossification may be crucial to allow successful healing ( Chilbule et al., 2016 ; Kitoh et al., 2014 ). Beyond this specific clinical setting, the results bring fundamental insights on the mechanisms of bone repair defects in pseudarthrosis and the role of PCs and FGFR3 in the essential step of cartilage-to-bone transformation during bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…All the humeral lengthening satisfied the patients and allowed independent perineal hygiene. Surgical results of limb lengthening in achondroplastic patients were previously reported in many studies;3) however, the studies that compared the surgical results among the three long bones were rare 12). Certainly, the relatively small number of subjects was a limitation of our study.…”
Section: Discussionmentioning
confidence: 87%
“…They further emphasized that limb lengthening of more than 50% of the initial length carries significant risk. [ 65 ] A retrospective study on intramedullary rodding of long bones in 16 children with OI showed that the frequency of fractures and the related complications were dramatically reduced after careful and precise implantation of either Sheffield rods or non-elongating rods of appropriate size. [ 66 ] An interesting report by Kaur et al .…”
Section: Resultsmentioning
confidence: 99%